Swimming at different temperatures: The lipid composition of sperm from three freshwater fish species determined by mass spectrometry and nuclear magnetic resonance spectroscopy. (July 2019) - Engel, Kathrin M.; Sampels, Sabine; Dzyuba, Borys; Podhorec, Peter; Policar, Tomáš; Dannenberger, Dirk; Schiller, Jürgen
Highlights: Differences in cholesterol and phospholipid content of different fish sperm. The lowest PUFA but the highest MUFA proportion in burbot sperm. Elevated amount of PUFA in northern pike sperm based on the n-3 fatty acids. Elevated SM content in carp sperm. Spot intensities of primuline-stained TLC plates yields different results than NMR. Abstract: The spawning behavior of different fish species is as diverse as their habitats. A lot of factors influence the (phospho)lipid composition of fish sperm, including the water temperature at which spawning takes place. Therefore, this study aimed on the elucidation of the phospholipid composition of sperm from three fish species from different orders (common carp – Cyprinus carpio, northern pike – Esox lucius and burbot – Lota lota ) with different spawning temperatures by nuclear magnetic resonance spectroscopy (NMR), matrix-assisted laser desorption/ionization mass spectrometry and thin-layer chromatography (TLC) coupled to electrospray ionization mass spectrometry as well as gas chromatography. Next to the lipid composition that was different for carp, northern pike and burbot, regarding the moieties of the different (phospho)lipid classes (particularly sphingomyelin and acidic phospholipids) and the saturation degree of the fatty acyl residues, there were differences observed depending on the analytical method that was used. The results from TLC and NMR investigations differed regarding the amounts of the different phospholipids. Reasons for these discrepancies are discussed in detail.